TEMPLE AND SURYA IN OC EO CULTURE IN SOUTHERN VIETNAM - Đặng Văn Thắng; Nguyễn Hữu Lý (Tạp chí Khoa học Đại học Đà Lạt)
Belief in the Surya of India was adopted into Oc Eo culture in Southern Vietnam from the 2nd century BC to the 7th century AD and existed until the end of Oc Eo culture from 7th century AD to 12th century AD. The first stage was a temple built in brick or stone with a circlar shape in the center and a golden Sun wheel with eight rays. The next stage was a temple built of bricks with a sandstone statue of the Sun god. In this study, the author updates the current knowledge about the temple and the statue of the Surya in Oc Eo culture in southern Vietnam. The article discusses the introduction, chronology, and developmental process of the symbol of the Surya in Oc Eo culture. Additional materials for the study of Oc Eo culture are found in Phu Nam in Southern Vietnam.